Accelerated aging of onion seeds (Allium cepa L.) submitted to saturated salt solution - Madruga de Tunes, Lilian; Tavares, Lizandro Ciciliano; Rufino, Cassyo de Araújo; Fernandes Vieira, Jucilayne; Dos Santos Acunha, Tanize; Souza Alburquerque Barros, Antonio Carlos; Briao Muniz, Marlove Fátima (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2012)
The objective of the present study was to evaluate the methodology of the accelerated aging test to evaluate the physiological potential of onion seeds, as well as verify the possibility of using unsaturated and saturated solutions of sodium chloride (NaCl) as an option for water uptake control in seeds during the test without reducing sensitivity. Five lots of onion seeds were tested for germination, seedling emergence, emergence speed and accelerated aging (periods of 24, 48, 72, or 96 hours, with or without the use of a saturated saline solution of NaCl). The use of unsaturated and saturated solutions of NaCl reduced water absorption by onion seeds during the accelerated aging test, resulting in a less pronounced rate of deterioration, and less drastic and more uniform results. The 48 hour treatment with unsaturated and saturated NaCl solutions is an option for use because it promotes a better classification of the onion seed lots at different vigor levels.